Uzbek-russian-English Code-Switching in Contemporary Urban Uzbekistan - Gulruhsor Oltiboyeva (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This study examines the structural patterns and sociolinguistic functions of Uzbek–Russian–English code-switching within the contemporary multilingual landscape of Uzbekistan. Grounded in qualitative sociolinguistic methodologies, the research analyzes naturally occurring conversational data and participant reflections to elucidate the mechanisms and motivations underpinning language alternation. Findings reveal a predominance of intra-sentential switching, with discernible functional differentiation between language pairs: Uzbek–Russian switching prevails in informal and technical discourse, while Uzbek–English switching emerges prominently in academic and digital domains. Code-switching practices are shown to be deeply intertwined with identity construction, signaling ethnic affiliation, educational attainment, and global orientation. Moreover, the study highlights generational divergences in switching behavior, reflecting broader socio-political and economic transformations. By situating code-switching at the nexus of globalization, national language policy, and post-Soviet identity negotiation, this research contributes to a nuanced understanding of multilingualism in transitional societies. The findings underscore the necessity for language policies that accommodate the complex realities of linguistic practice in an increasingly globalized Uzbekistan.